2013
DOI: 10.1002/jgrd.50712
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Deep Blue aerosol retrieval algorithm: The second generation

Abstract: [1] The aerosol products retrieved using the Moderate Resolution Imaging Spectroradiometer (MODIS) collection 5.1 Deep Blue algorithm have provided useful information about aerosol properties over bright-reflecting land surfaces, such as desert, semiarid, and urban regions. However, many components of the C5.1 retrieval algorithm needed to be improved; for example, the use of a static surface database to estimate surface reflectances. This is particularly important over regions of mixed vegetated and nonvegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
719
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 920 publications
(770 citation statements)
references
References 43 publications
(51 reference statements)
3
719
0
1
Order By: Relevance
“…The MODIS DT cloud screening algorithm without cirrus cloud test (1.38 µm test) has been used with the current retrieval together and a visual-check according to the RGB images. The surface parameterization is a MODIS DB similar approach [6] while the aerosol types are parameterized by adapting the MODIS DT algorithm [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MODIS DT cloud screening algorithm without cirrus cloud test (1.38 µm test) has been used with the current retrieval together and a visual-check according to the RGB images. The surface parameterization is a MODIS DB similar approach [6] while the aerosol types are parameterized by adapting the MODIS DT algorithm [5].…”
Section: Methodsmentioning
confidence: 99%
“…In the SAHARA algorithm, we follow a similar idea to the MODIS DB aerosol retrieval algorithm [6]. Statistical relationships of surface reflectance between different wavelengths were obtained.…”
Section: Surface Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Levy et al (2013) provide a detailed explanation of basic MODIS retrieval concepts and improvements to the DT algorithm in Collection 6 for aerosol products. In addition, Hsu et al (2013) give a detailed explanation of the DB algorithm improvements in Collection 6.…”
Section: Modis Satellite Instrumentsmentioning
confidence: 99%
“…This comparative analysis does not aim to be a validation study of the MODIS sensor since many works during the long history of the MODIS sensor on the Terra and Aqua platforms have sought to improve its features (these include Kaufman et al, 1997a, b;Tanré et al, 1997;Remer et al, 2002Remer et al, , 2005Remer et al, , 2006Hsu, et al, 2004Hsu, et al, , 2006Hsu, et al, , 2013Levy et al, 2007Levy et al, , 2009Levy et al, , 2010Levy et al, , 2013Levy et al, , 2015Sayer et al, 2013Sayer et al, , 2014 https://darktarget.gsfc.nasa.gov/atbd/overview, last access: 9 April 2018). However, compared to other areas of the world, no studies have been reported in the Caribbean region and in Cuba in particular (Papadimas et al, 2009;Mishchenko et al, 2010;Kahn et al, 2011;Bennouna et al, 2011Bennouna et al, , 2013Witte et al, 2011;Gkikas et al, 2013Gkikas et al, , 2016Levy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%